The Role of Entrepreneurial Activities, ICT and Energy Consumption in the Economic Growth: An Econometric Evidence of EU Countries - Adeel, Shahzada; Arshad, Zeeshan; Ahmed, Kaleem; Ullah, Sami (Pakistan Journal of Humanities and Social Sciences, 2025)
The objective of the study to develop the linkages between economic growth (GDP), energy consumption, information and communication technology (ICT), and total entrepreneurial activities (TEA) in 17 European Union countries over the period 2000-2023. Annual data were analyzed using co-integration tests such as Fisher, Kao, Westerlund, and Pedroni to determine the long-term relationship among the variables. The study also employed PMG to examine the long-run elasticities, as well as DOLS and DMOLS for robustness. The results indicated that increased entrepreneurial activities, energy consumption, and ICT lead to growth in GDP in the EU region. This means that in the current situation, entrepreneurial activities strongly contribute to robust economic growth, which may result in developing sustainable, stable and progressive societies/economies. Furthermore, the study noted bidirectional causality running between the considered variables.